DIAGNOSIS KESULITAN BELAJAR BANGUN RUANG SISI LENGKUNG DI KELAS XI SMKN 1 PERCUT SEI TUAN - Dhita Thivani Linch Hutabarat; Ainul Marhamah Hasibuan; Azizah Yusra Amaliyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine what causes students' learning difficulties in studying mathematics on curved side space geometry in class XI of SMKN 1 Percut Sei Tuan. This type of research is a descriptive type of research with a qualitative approach. The population in this study were all students of SMKN 1 Percut Sei Tuan. The sample in this study was 32 students of class XI of SMKN 1 Percut Sei Tuan. Data collection used questionnaires, interviews, and tests on curved side space geometry. Based on the results of the questionnaire instrument, there were 4 forms of learning difficulties including; students who felt they had difficulty because they did not understand with a percentage of 39.06%, students who felt they were not careful in doing the test with a percentage of 42.96, students who felt the test was difficult with a percentage of 13.28%, and students who did not know anything about curved side space geometry with a percentage of 4.68%. Then based on the results of the test instrument, there were criteria that caused students' learning difficulties including; students who experienced conceptual errors with a percentage of 12.5%, students who experienced errors in using arithmetic operations with a percentage of 9.68%, students who completed the test with an imperfect algorithm with a percentage of 8.43%, and students who completed the test carelessly with a percentage of 8.43%.